Lizard Wears Shades. A Spectacled Sphenomorphus (Squamata: Scincidae), from the Sacred Forests of Mawphlang, Meghalaya, North-east India - Datta-Roy, Aniruddha; Das, Indraneil; Bauer, Aaron M.; Tron, Ronald K. Lyngdoh; Karanth, Praveen (Zootaxa, 2013)
A new species of lygosomatine scincid lizard is described from the sacred forests of Mawphlang, in Meghalaya, north-eastern India. Sphenomorphus apalpebratus sp. nov. possesses a spectacle or brille, an unusual feature within the Scincidae, and a first for the paraphyletic genus Sphenomorphus. The new species is compared with other members of the genus to which it is here assigned, as well as to members of the lygosomatine genera Lipinia and Scincella from mainland India, the Andaman and Nicobar Islands, and south-east Asia, to which it also bears resemblance. The new taxon is diagnosable in exhibiting the following combination of characters: small body size (SVL to 42.0 mm); moveable eyelids absent; auricular opening scaleless, situated in a shallow depression; dorsal scales show a line of demarcation along posterior edge of ventral pes; midbody scale rows 27–28; longitudinal scale rows between parietals and base of tail 62–64; lamellae under toe IV 8–9; supraoculars five; supralabials 5–6; infralabials 4–5; subcaudals 92; and dorsum golden brown, except at dorsal margin of lateral line, which is lighter, with four faintly spotted lines, two along each side of vertebral row of scales, that extend to tail base. The new species differs from its congeners in the lack of moveable eyelids, a character shared with several distantly related scincid genera.